An easyguide to APA style - Schwartz, Beth M.; Landrum, R. Eric; Gurung, Regan A. R. (Thousand Oaks: Sage, 2021)
"Fully updated with content from the Seventh Edition of the Publication Manual of the American Psychological Association, An EasyGuide to APA Style 4e points out common APA style and formatting mistakes and how to avoid them while providing detailed examples and complete sample student papers written to conform to APA format. The authors illustrate not only how to write using APA style, but also what writing in APA style really looks like when your paper is complete. Written in a conversational and clear style, this guide will help anyone find their way through the maze of rules in the APA Publication Manual and become proficient in learning the fine points of APA style. The latest edition not only includes all relevant updates to the latest edition of the Publication Manual, but also includes updated scholarship, new and relevant examples for today's students, and two new sample student papers"--
Includes bibliographical references (pages 262-265) and index.
Keywords: Psychology -- Authorship -- Style manuals; Social sciences -- Authorship -- Style manuals